Legal coverage of electronic commerce and payment practices in Algeria: Analytical study of a sample of Algerian society - Laib, Fouzia; Azzouz, Karima; Allali, Sarah (Journal of Human Sciences, 2022)
This study aims to identify the reality of commerce and electronic payment in Algeria, where the theoretical side of this research paper dealt with the legal coverage of both variables from the point of view of the Algerian legislator (legal reality), while on the practical side, it touched on the reality of trade and electronic payment practices in Algeria by relying on Questionnaire form. The results of the study showed the lack of clarity of the legislation issued with regard to electronic commerce and electronic payment systems. As for the statistical analysis of the results of the questionnaire, it showed a modest increase in the turnout of Algerians towards electronic purchase and payment operations money. This requires raising confidence through clear regulation and strictness in dealing with all economic operators.